Latent tuberculosis infection prevalence in rural Madagascar. (5th August 2020) - Sadananda, Gouri; Knoblauch, Astrid M; Andriamiadanarivo, Andry; Razafindrina, Kimmerling; Ambinintsoa, Ideal; Rabetombosoa, Roger Mario; Pando, Christine E; Tsang, Lai Yu; Small, Peter M; Rakotosamimanana, Niaina; Grandjean Lapierre, Simon
Abstract: Background: Understanding latent Mycobacterium tuberculosis infection (LTBI) prevalence is crucial for the design of TB control strategies. There are no data on LTBI in rural Madagascar. Methods: Tuberculin skin tests were performed in 98 adults aged >15 y in five rural villages in the Ifanadiana district, Madagascar. Results: Of adults, 78.6% were positive for LTBI, ranging between 28.6% and 95.0% among villages. The majority (65.3%) showed an induration reaction of >15 mm. Conclusions: LTBI prevalence is high in rural Madagascar. Long-term TB control strategies including LTBI testing and treatment must account for high and heterogeneous prevalence in remote, underdeveloped areas.